SPREADING LAUGHTER THROUGH HUMOR FROM GRICEAN MAXIMS AND ISLAMIC PERSPECTIVES - Andini Anugrah Fitria; Zuliati Rohmah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Humor is essential in maintaining the balance of human life socially and psychologically. Each culture in the world, including Islamic culture, perceives humor differently. Furthermore, from an academic perspective, humor can be constructed using linguistic features. Therefore, this study aims to examine verbal humor construction using linguistics features and evaluate how verbal humor is perceived by different cultures, particularly popular British and Islamic cultures. British popular culture is directed more toward the liberal culture, which is often opposed to the Islamic culture, which is often seen as conservative. By employing a qualitative approach, the study investigates the verbal humor construction in Black Books comedy series using Gricean cooperative maxim theory and Marzolph's concept of Islamic perspectives on humor based on the Holy Qur’an and Hadith. The results of this study point out that verbal humor utterances in the series flout and violate all four Gricean maxims, which are the maxim of quality (54.3%), quantity (14.3%), relevance (11.4%), and manner (20%). This study also found that most verbal humor utterances in the series are appropriate to Islamic perspectives on humor, as 60% of the verbal humor utterances do not contain ridicule, defamation, offensive utterances and name-calling, and some other forbidden acts in Islam such as lies and abusive behaviors. The results of this study are expected to provide more insights into verbal humor construction and different cultures' perspectives on verbal humor.